Using of Activated Jurdiga for Bleaching of Sunflower Edible Oils - M. Mustafa1, Ayat; K. Abusabah1, Elnur (Gezira Journal of Engineering and Applied Sciences, 2019)
Bleaching process is cost intensive process for the refining vegetable oils and this is due to the consumption of bleaching earth which is imported from abroad which contributes in raising the total operating cost of the process. The objective of this study is to investigate the possibility of using activated jurdiga to bleach edible oils to meet the local demand and lower production cost. Jurdiga was brought from Um-Shoka area in Sennar State, Sudan. The chemical composition of jurdiga was determined. The analysis of jurdiga revealed high total sodium carbonate equal to 24 % and sodium bicarbonate equal to 20%. Jurdiga was crushed and was activated by 5%, 5%, 10% and 20% of concentrated   () . The bleaching efficiency of the produced activated jurdiga for bleaching of sunflower oil was investigated by adding various dosages of 1.5, 2.5, 3.5 and 4.5 grams of activated Jurdiga at temperatures of 80℃, 100℃ and 120℃ and compared with commercial fuller earth. The conditions that gave best results for the sulfuric acid activation and bleaching test was found to be 10% acid concentration, 4.5 grams of activated jurdiga at 120℃ for 70 gram of oil. The bleaching efficiency of the activated jurdiga was 70 %. This result is compararable with commercial fuller earth which has 90% bleaching efficiency.  Key words: Bleaching, Fuller earth, Activation, Jurdiga, Edible oils.